Check out this weird maths problem – can you see the error?

If                                                                                                      y = x
And                                                                                                y^2 = x^2

Then,                                                                                             xy = x^2
And,                                                                                      xy - y^2 = x^2 - y^2 (1)

Using ‘FOIL’:                                                             (x-y)(x+y) = x^2 - y^2 (2)

So, making equation(1) = equation(2),                     (x-y)(x+y) = yx - y^2
And,                                                                           (x-y)(x+y) = y(x-y)

Divide both sides by (x-y):                                                 (x+y) = y
Since x = y,                                                                           (y+y) = y
Therefore,                                                                                        2y = y

Divide both sides by y:                                                                       2 = 1

Subtracting 1 from both sides gives you:                                           1 = 0

Let me know if you can solve this maths dilemma or ask me if it begins to annoy you too much!